2019
DOI: 10.1021/acs.nanolett.9b02006
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-up Atomically Thin Coplanar Semiconductor–Metal Circuitry via Phase Engineered Chemical Assembly

Abstract: Two-dimensional (2D) layered semiconductors, with their ultimate atomic thickness, have shown promise to scale down transistors for modern integrated circuitry. However, the electrical contacts that connect these materials with external bulky metals are usually unsatisfactory, which limits the transistor performance. Recently, contacting 2D semiconductors using coplanar 2D conductors has shown promise in reducing the problematic high resistance contacts. However, many of these methods are not ideal for scaled … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 31 publications
2
76
0
Order By: Relevance
“…The result confirmed a higher work function of the 1 T′-MoTe 2 than that of the 2H-MoTe 2 . The higher work function of the 1 T′-MoTe 2 is preferable for the ohmic contact of the p-type 2H-MoTe 2 , which is consistent with our previous transport data 38,43 .…”
Section: Resultssupporting
confidence: 92%
“…The result confirmed a higher work function of the 1 T′-MoTe 2 than that of the 2H-MoTe 2 . The higher work function of the 1 T′-MoTe 2 is preferable for the ohmic contact of the p-type 2H-MoTe 2 , which is consistent with our previous transport data 38,43 .…”
Section: Resultssupporting
confidence: 92%
“…155 Interestingly, in MoTe 2 , lateral 1T 0 /2H homojunctions can be obtained via direct CVD synthesis. 160,243,244 The contact barrier height at the lateral 1T 0 /2H interface is reported to be as low as 25-30 meV, 160,243 and in the coplanar 1T 0 /2H contact MoTe 2 FET, the channel mobility reached 16.2 cm 2 V À1 s À1 at room temperature. 243 5.4.…”
Section: How Stable the Metastable 1t(1t 0 ) Phases Are?mentioning
confidence: 99%
“…Recently, creating 2D heterostructures between two TMDs with different phase structures, called heterophase junctions, have attracted great research interest, because the modulation of phase structure in 2D heterojunction can endow more degree of freedom for building new interface structures and exploring novel properties and applications. [ 15–20 ] For example, a novel topologically protected helical edge states were discovered at the 1T′‐2H heterophase interface in WSe 2 monolayer. [ 21 ] In addition, Zhang et al found that the 1T′‐2H heterophase interface in MoS 2 monolayer can greatly enhance the catalysis activity for hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%